Temporal characteristics of physicochemical parameter of juvenile mosquito (diptera: culicidae) breeding media in rural area / Mohammed Fadli Fasanai - Fasanai, Mohammed Fadli (2018)
Introduction: Dengue fever is a mosquito-borne disease, very infectious and remains to be one of the major public health problems around the world. Aedes mosquitoes; Ae. aegypti and Ae. albopictus in particular, are known to be important vectors in carrying Dengue viruses and spreading it to human hosts. Objective: The objective of this study was to assess the physicochemical characteristics in waters that lead to the selection for breeding by adult mosquitoes. Methodology: An extensive entomological survey has been conducted in four villages in Sukau Subdistrict for 12 weeks to find out the distribution of the Aedes larva in relation to the temporal physicochemical characteristics of the breeding water. Results: The most efficient container types found which have the most abundant mosquito larva are container glass containers (CID7 = 17 %) and followed by tires (CID1 = 13 %.), and plastic containers (CID3 = 12 %). All water samples (n=100) collected were tested for physicochemical parameters in order to measure the water quality of the oviposition containers and it was found that there were strong relationship between the presence of Aedes immature with pH (p-value = 0.001; range: 7.13 – 7.62), turbidity (p-value = 0.001; range: 9.70 – 12.80), and total coliform (p-value = 0.001; range: 71.33 – 131.35). Other parameter showed a weak relationship, but may also contribute to the breeding selection for Aedes adults. Conclusion: This study found that the prevalence of Ae. albopictus in the container-breeding habitats echoed its significance as the principal vector for dengue. The physicochemical characteristics of breeding sites can be manipulated to be integrated into the Dengue Management Program to control Aedes population.